-(8-b)+12b-9=-6b+2b

Simple and best practice solution for -(8-b)+12b-9=-6b+2b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(8-b)+12b-9=-6b+2b equation:


Simplifying
-1(8 + -1b) + 12b + -9 = -6b + 2b
(8 * -1 + -1b * -1) + 12b + -9 = -6b + 2b
(-8 + 1b) + 12b + -9 = -6b + 2b

Reorder the terms:
-8 + -9 + 1b + 12b = -6b + 2b

Combine like terms: -8 + -9 = -17
-17 + 1b + 12b = -6b + 2b

Combine like terms: 1b + 12b = 13b
-17 + 13b = -6b + 2b

Combine like terms: -6b + 2b = -4b
-17 + 13b = -4b

Solving
-17 + 13b = -4b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '4b' to each side of the equation.
-17 + 13b + 4b = -4b + 4b

Combine like terms: 13b + 4b = 17b
-17 + 17b = -4b + 4b

Combine like terms: -4b + 4b = 0
-17 + 17b = 0

Add '17' to each side of the equation.
-17 + 17 + 17b = 0 + 17

Combine like terms: -17 + 17 = 0
0 + 17b = 0 + 17
17b = 0 + 17

Combine like terms: 0 + 17 = 17
17b = 17

Divide each side by '17'.
b = 1

Simplifying
b = 1

See similar equations:

| 1=x-6 | | 3(2x-1)+2=5x-1 | | x+4y+2z=0 | | 2x-3y+2=2 | | 6+4a=-8 | | 0.66r=8 | | 72=-3(x+4)-21x | | K-7=10 | | 3+z=18 | | 1.5r=8 | | -5x=18-3x | | 0.8m=80 | | -6+4y=-12 | | 5x-4(x-6)=1 | | h=-16t^2+150t+1 | | 2x+y=10-3x | | 2x^2-15x+15=8-x^2-5x | | (u+3)2=2u+11u+15 | | X^4-7x+3=0 | | 2x^4-7x+3=0 | | 2x+3x-15=25 | | -2+x-4x=11 | | 5(6)+3(7)= | | -4+3x=-12+25xfraction | | 2y-4*0=10 | | x-2 = 9 (4-10x)4 | | 9y-5y-9=48.80 | | W-8=23 | | 2y+-4*-2=10 | | -42=-6(z-3) | | 5x+9=82-8x | | -3k^2g-[4kg^2-(6k^2g-2kg^2)]=0 |

Equations solver categories